Targeted inhibition of phosphatidyl inositol-3-kinase p110β, but not p110α, enhances apoptosis and sensitivity to paclitaxel in chemoresistant ovarian cancers - Jeong, Ju-yeon (Springer US, 2013)
The phosphatidylinositol 3-kinase (PI3K) pathway is one of the critical signaling cascades playing important roles in the chemoresistance of human cancer cells, including ovarian cancer. In this study, we investigated the potential of targeting the PI3K p110β-isoform as a novel approach to overcome the chemoresistance in ovarian cancer. The effects on apoptosis, cell viability, proliferation and migration in chemoresistant ovarian cancer cell were determined following targeted p110β inhibition by small interfering RNA (siRNA). Seven paclitaxel (PTX)-resistant sublines (SKpacs and A2780pac) were produced from SKOV3 and A2780 ovarian cancer cell lines. We, first, evaluated the expression of PI3K p110 isoforms in chemosensitive and chemoresistant ovarian cancer cell lines and patient specimens, and found that p110β-isoform was significantly overexpressed both in a panel of ovarian cancer samples, and in PTX-resistant sublines compared with their parent cell lines. RNA interference-mediated p110β silencing augmented PTX-mediated apoptosis (31.15 ± 13.88 %) and reduced cell viability (67 %) in PTX-resistant cells, whereas targeting p110α did not show a significant change in cell viability and apoptosis. In addition, p110β silencing impaired cell proliferation (60 %) in PTX-resistant SKpac cells. We also found the combined treatment group with p110β siRNA and PTX showed a significant inhibition of tumor growth of SKpac cells compared to the PTX-only treated group in a xenograft nude mouse model. Thus, the siRNA-mediated silencing of PI3K p110β resensitizes PTX-resistant ovarian cancer cells, and may be a useful therapeutic strategy for PTX-resistant ovarian cancers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10495-013-0807-9) contains supplementary material, which is available to authorized users.